A two-gene methylation signature for the diagnosis of bladder cancer in urine. (1st February 2019) - Bosschieter, Judith; Nieuwenhuijzen, Jakko A; Hentschel, Anouk; van Splunter, Annina P; Segerink, Loes I; Vis, André N; Wilting, Saskia M; Lissenberg-Witte, Birgit I; A van Moorselaar, R Jeroen; Steenbergen, Renske DM
Aim: To analyze the potential of 14 cancer-associated genes, including six miRNAs, for bladder cancer (BC) diagnosis in urine.Patients & methods: DNA methylation levels of 14 genes were analyzed in urine of 72 BC patients and 75 healthy controls using quantitative methylation-specific PCR. Multivariate logistic regression analysis was used to determine an optimal marker panel.Results: Ten genes were significantly hypermethylated in BC patients. The GHSR/MAL combination showed the best diagnostic performance, reaching a sensitivity of 92% (95% CI: 86–99) and a specificity of 85% (95% CI: 76–94).Conclusion: We identified a novel two-gene panel with a high diagnostic accuracy for BC that can be applied in a noninvasive, urine-based test.